The Effectiveness of Implementing Daily Journaling on The Anxiety of Mother Children With Hemophilia - Puswati, Desti; Rahmadini, Irena; Nita, Yureya; Devita, Yeni; Alfianur, Alfianur (Jurnal Keperawatan Priority, 2024)
The anxiety of mothers who have children with hemophilia can be overcome in various ways, including daily journal writing therapy. The research aims to determine the effectiveness of implementing a daily journal in reducing the anxiety of mothers who have children with hemophilia at HMHI Riau: quantitative research type, quasi-experimental design, one group pre-test post-test—carried out the research from January to June 2023. Samples were taken using a total population technique of 25 respondents. The research instrument used the HARS (Hamilton et al.), which consists of 14 items. This research has passed ethical test no. 067/STIKES PN/KEPK/V/2023. Before the intervention, respondents filled out personal and anxiety data questionnaires. Then, respondents were given a notebook to write down what they felt every day, and their anxiety level was measured again. The research results showed that the average level of maternal anxiety decreased by (7.56%) before the intervention (27.00) and after the intervention (19.44), p-value 0.000 < 0.05. So, H0 was rejected, which means that the daily journal is effective in reducing the anxiety level of mothers who have hemophilic children at HMHI Riau. The research results showed that the majority of respondents had the same anxiety both before and after the intervention, namely feeling afraid about their thoughts about their children; they are worried that their child will experience injury or bleeding during their daily activities. It recommended that future researchers create a digital program to overcome anxiety in mothers with hemophilia.